2018
DOI: 10.1016/j.nima.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

The socio-economic impact of a breakthrough in the particle accelerators’ technology: A research agenda

Abstract: Preliminary evidence on the long-run trajectory of the accelerator industry suggests that it may be close to the maturity phase of its cycle. If this is the case, how can we measure the benefits of an uncertain breakthrough in acceleration technology? Who are the main stakeholders interested by such a breakthrough? We identify these subjects and sketch some avenues for answering these questions.We thus present a model for the social Cost-Benefit Analysis (CBA) of research infrastructures and illustrate the res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…New solutions developed for research purposes by CERN with the involvement of the industry have found applications in many fields including computing, medical, biomedical and aerospatial technologies (Battistoni et al, 2016;Florio et al, 2018a;Jewell, 2008), suggesting the importance for society as a whole of its activities, due to the spillovers in several fields and across different actors.…”
Section: Cern: Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…New solutions developed for research purposes by CERN with the involvement of the industry have found applications in many fields including computing, medical, biomedical and aerospatial technologies (Battistoni et al, 2016;Florio et al, 2018a;Jewell, 2008), suggesting the importance for society as a whole of its activities, due to the spillovers in several fields and across different actors.…”
Section: Cern: Backgroundmentioning
confidence: 99%
“…By virtue of the sheer size of their research infrastructures and scientific instruments and the generous budget they manage, procurement from Big Science Centers (BSCs) has the potential of being an important tool for the innovation policies of governments funding them. While BSCs are purposefully built to address broad and complex research questions, their Member States (MS) fund them not only for the promise of scientific discoveries, but also for the the economic and societal spillovers they can generate (Autio et al, 2004;Florio et al, 2018a;Helmers and Overman, 2017;Vuola and Hameri, 2006). For this reason, the procurement rules of several European BSCs incorporate, or are inspired by, the socalled juste retour principle.…”
Section: Introductionmentioning
confidence: 99%
“…A social CBA is an appropriate methodology for evaluating a RI because it translates in quantitative terms the multi-dimensional benefits ascribed to it [10]. The social CBA machinery has found applications in several policy-relevant contexts.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of the sheer size of their research infrastructures, scientific instruments and the generous budget they manage, public procurement from Big Science Centers (BSCs) can be an important tool for the innovation policies of governments funding them. While BSCs are purposefully built to address broad and complex research questions, their Member States (MS) fund them not only for the promise of scientific discoveries, but also for the the economic and societal spillovers they can generate (Autio et al, 2004;Florio et al, 2018a;Helmers and Overman, 2017;Vuola and Hameri, 2006). For this reason, the procurement rules of several European BSCs incorporate, or are inspired by, the so-called juste retour concept.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1, the LHC is part of an accelerator complex, namely a succession of machines with increasingly higher energies (Evans, 2016). Each machine accelerates a beam New solutions developed for research purposes by CERN with the involvement of the in-dustry have found applications in many fields including computing, medical, biomedical and aerospatial technologies (Battistoni et al, 2016;Florio et al, 2018a;Jewell, 2008), suggesting the importance for society as a whole of its activities, due to the spillovers in several fields and across different actors.…”
Section: Introductionmentioning
confidence: 99%